High-intensity focused ultrasound (HIFU) combined with gonadotropin-releasing hormone analogs (GnRHa) and levonorgestrel-releasing intrauterine system (LNG-IUS) for adenomyosis: a case series with long-term follow up. (1st January 2019) - Haiyan, Sun; Lin, Wang; Shuhua, Huang; Wang, Wei
Abstract: Objective: This research was conducted to assess the long-term outcomes of a combination treatment of High-intensity focused ultrasound (HIFU) ablation, gonadotropin-releasing hormone analogs (GnRHa) and Levonorgestrel-releasing intrauterine system (LNG-IUS) for women with adenomyosis (AD). Methods: One hundred and forty-two patients with AD were enrolled and treated with HIFU conservative treatment in combination with adjuvant therapy of GnRHa and LNG-IUS. All the cases were followed up to 5 years after treatment. The volumes of uteri, AD lesions, and menstrual blood, and dysmenorrhea scores were measured. Also, the incidences of recurrence and complications were recorded. Results: Both the uterine and lesion volumes significantly decreased after treatment. The uterine volume gradually reduced after treatment, reaching the lowest level of 122.07 ± 44.12 cm 3 at 12 months after treatment, with an average reduction rate of 45%, and then increased slightly, maintaining a reduction rate of about 35% compared with the baseline level. Similar decreases in AD lesion volumes, dysmenorrhea scores, and menstrual flow were also demonstrated. Hemoglobin levels increased. Moreover, the long-term recurrence rates were low, with 5.68% and 7.91% in dysmenorrhea and menorrhagia, respectively. No serious complications or adverse events were reported. Conclusions: HIFU ablation, in combination with GnRHa and LNG-LUS, might be a safe and effective alternative in the treatment for women with adenomyosis.